OBSTACLES FACED BY TEACHERS IN SHAPING STUDENT CHARACTER VALUES AT SD NEGERI 16 BANDA ACEH - Putri Lara Maulida; Siti Mayang Sari; Fitriani Manurung; Sariakin (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The aim of this research is to find out the obstacles faced by teachers informing the character of students and to find out the efforts made by teachersin forming the character of students. This research uses qualitative researchmethods with a qualitative descriptive design. This research was carried outon the basis of a phenomenon that occurred in one case at SD Negeri 16Banda Aceh. Researchers found several students' behavior that did not reflectthe character values within the students. Researchers suspect that the declinein character values among students at these schools is due to the formation ofcharacter values which is still not comprehensive, as well as the existence ofvarious factors experienced by students, which can influence the formation oftheir character values. This research describes how teachers make efforts toshape students' character values and what obstacles teachers face in formingstudents' character values. Data was collected through observation, interviewsand documentation. The results of the research show that the obstacles facedby teachers in forming students' character values are: 1) the schoolenvironment and school facilities and infrastructure that are less supportive; 2)environmental factors (family and community environment); 3) lack ofteacher role models. Meanwhile, the teacher's efforts in forming students'character values are: a) religious character b) honest character c) disciplinedcharacter.